PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL FLIPBOOK UNTUK MENINGKATKAN PEMAHAMAN KONSEP IPA PADA PESERTA DIDIK DI MI AL-ADLI PALEMBANG - Masykuria Luthfia Ananda; Middya Boty; Yunita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research is an R&D (Research and Development) development research that aims to determine the results of the validity and practicality of the developed media and test the effectiveness of digital flipbook learning media to improve understanding of Natural Sciences (IPA) concepts in grade IV students at MI Al-Adli Palembang. This research is based on the lack of maximum understanding of students' concepts in science subjects, especially on material changes in the form of objects due to the use of learning media that are less interactive and interesting. This research uses the ADDIE development model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. The research instruments used included expert validation sheets involving lecturers as media and language experts, student questionnaires for practicality tests involving 24 students of class IV B as samples, as well as pre-test and post test learning outcomes tests for effectiveness tests. The results of the study show that the digital flipbook learning media developed is very valid with a percentage score of 88% media experts, 86% linguists and 92% material experts. The students' response to the practicality of the media was very practical with a percentage score of 88.13%. and the results of the pre test and post test with the effective category were obtained with a percentage of 80.07%. Thus, the digital learning media of flipbooks is suitabel for use as an interactive learning media in madrasah ibtidaiyah